Molybdenite as a rhenium carrier : first results of a spectroscopic approach using synchrotron radiation - Silva, Teresa (2014)
The chemical and physical properties of rhenium render it a highly demanded metal for advanced applications in important industrial fields. This very scarce element occurs mainly in ores of porphyry copper-molybdenum deposits associated with the mineral molybdenite, MoS2, but it has also been found in granite pegmatites and quartz veins as well as in volcanic gases. Molybdenite is a typical polytype mineral which crystal structure is based on the stacking of [S-Mo-S] with molybdenum in prismatic coordination by sulphide anions; however, it is not yet clearly established if rhenium ions replace Mo4+ cations in a disordered way or else, if such replacement gives rise to dispersed nanodomains of a rhenium-rich phase. As a contribution to clarify this question, an X-ray absorption spectroscopy (XANES) study using synchrotron radiation was performed at the Re L3-edge of rhenium-containing molybdenite samples. Obtained results are described and discussed supporting the generally accepted structural perspective that rhenium is mainly carried by molybdenite through the isomorphous replacement of Mo, rather than by the formation of dispersed Re-specific nanophase(s).